INFLUENCE OF CULTURAL FERTILIZERS AND ADDITIONAL FEEDINGS ON THE PRODUCTION INDICATORS OF WINTER WHEAT VARIETIES (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Winter soft wheat varieties have a high demand for microelements and macro-elements during the growth period, while the lack of these elements has a negative effect on wheat productivity. Of soft wheat in our experiments. Jasmine. variety N180P90K60 kg/ha feeding with a suspension of macro- and micro-fertilizers at the rate of 60 kg/ha increased the average number of productive stems by 2.5 pieces, the length of the spike by 4.3 cm, the number of spikes in the spike by 7.5, and the number of grains in the spike by 23.4 allowed.